Sobriety, social capital, and village network structures. (June 2023) - Murphy, David M.A.
Highlights: I analyze data from an RCT in Kenya to determine whether an alcohol remission intervention affected peer relationships and network structures. Results show that two peers randomly assigned to the treatment increase their relationship strength compared to two peers in the control. Two nearby same-gender treatment peers are 9 percentage points more likely to have an agricultural information link with their peer. Treated individuals increase their closeness centrality in agricultural information networks by 0.38 standard deviations. Study suggests indirect benefits on relationship outcomes and community social capital from substance abuse programs and self-help programs. Abstract: External shocks or stimuli can have significant effects on community network structures, which in turn can affect relationship ties and social capital. To this point, however, few studies analyze impacts of self-help programs, such as those targeting substance abuse, on network structures or measures of social capital. This study analyzes the effects of a randomized control trial (RCT) in western Kenya that included an intervention aimed at decreasing alcohol abuse using group therapies and spousal level counseling. Using dyadic network data collected from alcohol-using households, the analysis finds that two nearby same-gender peers randomly assigned to the treatment group are 9 percentage points [pp] more likely to have an agricultural information link with their peer and 8 pp more likely to work with their peer compared to two individuals in the control group. Additional individual-level results find that assignment to the treatment significantly increases an individual's network centrality as measured by degree, closeness, and betweenness. I explore potential mechanisms and find evidence suggesting network effects at the intensive and extensive margin and the development of support linkages all likely contributed to these results. This study shows that programs utilizing peer effects can not only have positive impacts on alcohol consumption, but also positive spillover effects on relationship ties and on a treated individual's network centrality. The results thus suggest significant positive impacts of the program on social capital, and points to the indirect benefits of substance abuse programs (and self-help programs in general) on communities.